DAMPAK KEPEMIMPINAN PASILOG BEKANG DALAM MENINGKATKAN KUALITAS PELAYANAN PENDISTRIBUSIAN KAPORSATLAP DI YONBEKANG 1/TBY/1 KOSTRAD - Mariani P, Agustina Dwi; Ixbal, Gading; Soemantri, Ade; Putri, Windy Kartika (PPM Sdirjianbang Akademi Militer, 2025)
Commander (Danton) must be able to maintain and even improve his professionalism in order to achieve the established vision and mission. A leader plays a strategic role in an organization, because without the role of an ideal leader, there will be no constructive collective effort in achieving common goals. Yonbekang 1/TBY/1 Kostrad is one of the transportation support units (Bekang) in Kostrad (Army Strategic Command), which holds an important role in supporting military operations by providing logistics, transportation, and supplies support. This research aims to determine how the leadership impact of the Logistics Officer (Pasilog) can improve the quality of logistics distribution services in Yonbekang 1/TBY/1 Kostrad.